The kid - Sapphire (: Penguin, 2012, ©2011.)
ssues. Abdul Jones is nine years old when his mother Precious dies. Parentless, he is sent first to a foster home and then to a Catholic orphanage. But the priests charged to care for him abuse his trust terribly. And Abdul, a victim, finds that he reacts in the most frightening way imaginable. Soon he is trapped in a dark cycle of sexual violence and betrayal. Yet through dance, in controlling his body, he